Development of the National Priority Rural Area of Pandeglang Banten - Muhlis, Taufik; Rustiadi, Ernan; Munibah, Khursatul (ASTONJADRO, 2023)
Pandeglang Regency, Banten Province, is one of the regions on the island of Java that has great economic potential from a geographical perspective in the fisheries, agriculture, and tourism sectors to support the development and the economy in the area. However, since the tsunami hit this area in 2018, plus the non-natural catastrophe at the beginning of 2020, namely Covid-19, it has paralyzed the joints of the economy, which has an impact on hindering development in Pandeglang Regency. The purpose of this research is to discover the development of the Pandeglang rural area after the establishment of village funds and natural and non-natural disasters, to find out which locations are recommended and what steps are taken to accelerate economic recovery. This study uses analysis techniques of tabular and spatial data time series, descriptive analysis of tabular and spatial data comparisons, spatial pattern analysis using Moran's index value, and LISA method analysis. Based on the study results, three villages were recommended as centers for KPPNs, namely Teluk Village, Caring Village, and Sukacai Village. Based on the analysis results, Teluk Village and Caringin Village are villages affected by the tsunami, and Sukacai Village is a difficult village to develop in the 2015-2021 range.